Sedition (Crime of) - Rebollo Vargas, Rafael (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The sedition crime is located systematically in the Penal code as a crime against the public order, for what its object of tutelage and its ends not at all they have to do with a «rebellion in child», although some recent resolutions of the National Audience and of the proper Supreme Court denature it up to the point of attributing to him a few purposes that do not correspond to its current typical configuration.